Cooperative Beamforming for Physical-Layer Security in Power-Constrained Wireless Sensor Networks with Partial Relay Selection. (24th March 2016) - Qian, Mujun; Liu, Chen; Zou, Yulong
Abstract : We investigate the physical-layer security of a wireless sensor network comprised of a source-destination pair, multiple decode-and-forward (DF) relays, and an eavesdropper. When the relays forward the source signal to the destination, they should dissipate certain power for driving their physical circuits (e.g., amplifiers and filters), in addition to the transmit power required for emitting radio signals. However, no existing work considers the circuit power when exploiting relays for enhancing the wireless security against eavesdropping. We thus propose the relay-selection based cooperative beamforming framework, where partial relays are selected to forward the source signal in a beamforming manner. We present two relay-selection strategies, namely, the exponential-complexity exhaustive search and linear-complexity relay ordering. For comparison purposes, we also evaluate the conventional all-relay based and best-relay based beamforming schemes, where all relays or only the best one is selected to assist the source-destination transmission. It is shown that the proposed beamforming schemes significantly outperform the conventional all-relay and best-relay based beamforming schemes in terms of secrecy capacity. Additionally, the relay-ordering based beamforming scheme almost achieves the same secrecy capacity as the exhaustive-search method, but with a reduced computational complexity.